Training is the foundation of security. Issue 8 (August 2021) - Paterson, Oliver
Abstract : No business, no matter what its size, is immune from the threat of a cyber attack. This is evidenced by the number of cases rising year on year, particularly during the height of the pandemic, with the UK's National Cyber Security Centre (NCSC) reporting a 20% increase in serious incidents compared to 2018-2019. Cyber attacks are also becoming more innovative and we're already seeing an increase in new and advanced tactics, such as fileless malware and crypto-miners.